Konsentrasi merkuri ikan capungan Cardinalfish (Sphaeramia orbicularis) di area budidaya perairan Pintu Kota Kecamatan Lembeh Utara, Bitung - Sabono, Mateda M.; Undap, Suzanne L.; Longdong, Sammy N. J. (Universitas Sam Ratulangi, 2020)
The aims of this research were to determine the total mercury concentration of Cardinalfish (Sphaeramia Orbicularis) and the waters in aquaculture area of Pintu Kota, North Lembeh, Bitung, and its water quality paramaters (temperature, salinity, pH). The research was conducted from June to Nopember 2019 in the cultivation area of tiger grouper fish in which the fish and seawater were sampled and analyzed in the laboratory. Determination stations were done by purposive sampling which refers to the physiographic lacation wherever possible in order to represent or describe these waters. Station 1 represented the sea transpartion port of Lembeh Island (no cultivation), Station 2 where the cultivation A, Station 3 where the cultivation B. The results showed the concentrationÂ of the mercury obtained at Station 1 ranged from 0.00756 -0.00789 ppm, Station 2 ranged 0.00394-0.00418 ppm, and Station 3 ranges from 0.00506-0.00564 ppm. Whereas the concentration of mercury in seawaters samples were detected at Station 1, 2, and 3 were < 0.003 ppm. The temperature ranged between 26.2 â€“ 26.7Â°C, pH 7 and salinity 30-33 ppt. In general, the existence of the phisycal chemical parameters of water was in good measurement after comparing with the water quality standard of Kep. MENLH No. 51/2004. Mercury concentrations in all samples in Pintu Kota waters of North Lembeh as compared to WHO/FDA standard are still in good condition but have been already contaminated by mercury.